1999
DOI: 10.1111/j.1600-079x.1999.tb00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and the reduction or alleviation of stress1

Abstract: In a double blind and placebo controlled study designed to investigate the effect of melatonin administration at 13:00 hr on menstrual characteristics, prolactin, and premenstrual syndrome-like symptoms during simulated eastward travel, it was noted that melatonin reduces or alleviates the stress associated with the simulated travel. Bright lights were utilized to simulate eastward movement across six time zones. Melatonin (10 mg) was given to healthy females for 5 consecutive days during the late follicular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…In a double blind placebo controlled study, oral melatonin was found to reduce stress associated with simulated travel in humans. 28 In this study, the two week course of melatonin treatment did not significantly change the frequency of defecation or stool type. It also did not change rectal pressures during squeezing, pushing, or resting states.…”
Section: Discussionmentioning
confidence: 48%
“…In a double blind placebo controlled study, oral melatonin was found to reduce stress associated with simulated travel in humans. 28 In this study, the two week course of melatonin treatment did not significantly change the frequency of defecation or stool type. It also did not change rectal pressures during squeezing, pushing, or resting states.…”
Section: Discussionmentioning
confidence: 48%
“…1 Apart from the above functions, melatonin is involved in modulating stress-induced psychological and behavioural disturbances. 3 The finding that the concentration of melatonin in the gastrointestinal tissues surpasses that in the blood by 10-100 times 4 suggests melatonin may also play an important role in the digestive system. 2 In a double-blinded and placebo-controlled study, oral melatonin was found to reduce stress associated with simulated travel in humans.…”
Section: Introductionmentioning
confidence: 99%
“…For example, interactions between the pineal gland and hypothalamus-pituitary-adrenal (HPA) axis are well established (e.g., Maestroni et al 1989;Khan et al 1990; Kirby et al 1999). The HPA axis mediates responses to stressors such as predation events or limited food availability by increasing glucocorticoid secretion (Harvey et al 1984;Schwabl et al 1985;Wingfield 1988).…”
Section: Geographic Variation In Timekeeping Systems Among Three Popumentioning
confidence: 99%